Influence of high temperature on the flexural properties of GF/pCBT laminates and their fusion-bonded joints. (1st February 2017) - Zhang, Lu; Zhou, Limin; Zhang, Jifeng; Wang, Zhenqing; Lu, Shaowei; Wang, Xiaoqiang
Abstract: The glass fiber reinforced poly cyclic butylene terephthalate (GF/pCBT) composite laminates and their fusion-bonded joints were prepared at appropriate polymerization temperature. The connection types of joints were designed and optimized. A series of bending tests were conducted to research their mechanical behaviors at different temperatures. Experimental results showed that flexural properties of laminates and joints decreased as temperature increased. The temperature sensitivity of specimens changes in the temperature range from 50 °C to 75 °C due to the glass transition of the pCBT matrix. Furthermore, the failure modes of GF/pCBT composite joints were investigated at room and high temperature. In addition, the specimens suffered by different high temperatures ranging from 25 °C to 200 °C were cooled and then tested at room temperature. The results indicated the flexural strength of laminates was nearly constant after experience of high temperature, and increased slightly when the temperature is above 175 °C. The flexural strength of fusion-bonded joints was not affected by high temperature.